Pengaruh Kepercayaan Masyarakat dan Kompetensi Sumber Daya Pengelola Terhadap Kinerja Laba LPD - Widianata, Bina Putra; Budiasa, Gede Sujana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 4, April 2017 (pp. 472 - 676), 2017)
This study was conducted to determine the effect of public confidence, competence resource managers on the performance of profit by lending as an intervening variable in Gianyar district LPD. Data were obtained from literature studies, observations, interviews, and questionnaires. Filling out the questionnaire measured by Likert scale. Data analysis method used is the method of Structural Equation Modelling  (SEM) . This research method is intended as a draft to find and explain the relationship or the influence of variables through hypothesis testing (Explanation Research). Based on SEM Test PLS may otherwise 1). Public confidence and competence resource managers are not positive and significant impact directly on the performance of profit, 2). Public confidence and competence of the management of resources and the significant positive effect on the loan portfolio, 3). Loan disbursement positive and significant impact directly on the performance of earnings, and 4) the public Trust and competence Resources business and significant positive effect on earnings performance through lending, which can be called full mediation.
Keywords: Kepercayaan Masyarakat, Kompetensi Sumber Daya Pengelola, Kinerja Laba, Penyaluran Kredit